Pengaruh Ekstrak Etanol Daun Tapak Dara (Catharanthus roseus L.) dan Kolkisin terhadap Perkecambahan Biji Cabai Rawit Hibrida (Capsicum annuum) - Purwanti Pratiwi Purbosari; Etika Dyah Puspitasari (Universitas Sebelas Maret, 2018)
Catharanthusroseus L. contain vincaalcaloid compound. The leaf extract of Catharanthusroseus L. has anti-mitotic effect like colchisine which can cause chromosome duplication. The aim of this research was to evaluate the ethanolicleaf extract ofCatharanthusroseus L. and colchisine on seed germination of Capsicum annuum. 20 Seeds of Capsicum annuum were soaked for 24 h in ethanolic leaf extract of Catharanthusroseus L. (0,05%, 0,1% dan 0,5%), colchisine (0,05%, 0,1% dan 0,5%) and water as control. Seed germination percentage was observed and plant height was measured after 30 days. The 0,5% ethanolic leaf extract and 0,5% colchisine caused the lowest germination percentage. The 0,5% leaf extract caused the lowest average plant height and based on Tukey’s HSD test, soaked in 0,5% ethanol leaf extract treatment and other treatments are significantly different (P<0,05).